Reconstruction of the soft tissue defects of hand and wrist with ulnar artery perforator flap-presentation of case series - Das, Dibyendu (International Surgery Journal, 2022)
Reconstruction of soft tissue defect of hand and wrist is a common problem to plastic surgeon. I reconstructed the defect, both dorsal and palmar surface with a perforator-based flap from ulnar artery. The aim of the present study is to evaluate ulnar artery perforator flap in soft tissue defect of hand and wrist. Between January 2018 to February 2021, seven cases of skin defect were reconstructed with a perforator-based flap from ulnar artery, either pedicled or propeller type flap. The study was done at NRS medical college, Kolkata, where I have evaluated the viability of the flap, post-operative complication and patient’s satisfaction. All flaps survived, only in one case there was marginal necrosis that was treated conservatively. There was no post-operative complication, all flaps were doing well in six month and one year and one and half year follow up and patient’s satisfactions were also good. Ulnar artery perforator based fasciocutaneous flap, pedicled or propeller provides a reliable coverage of soft tissue defects of hand as well as wrist.